Enhancing the stability of anthocyanins: effects of encapsulation and drying in black grape juice powder - Ijod, Giroon; Mesran, Nur Fatinah; Mohamed Nawawi, Nur Izzati; Ismail-Fitry, Mohammad Rashedi; Abd Rahim, Muhamad Hafiz; Mohd Adzahan, Noranizan; Mohamad Azman, Ezzat (Codon Publications, 2026)
Plant-based beverages are one of the fastest-growing sectors in the food and beverage industry. However, the short shelf-life and lower stability of its liquid form required conversion into a stable instant juice powder, with enhanced shelf life. Microencapsulation via spray-drying protects sensitive bioactive compounds, such as anthocyanins, from degradation. This study evaluated the impact of different encapsulating agents (EAs) and inlet temperatures on the stability of anthocyanins and the physicochemical properties of spray-dried black grape juice powder. Maltodextrin (MD) and gum Arabic (GA) were used as EAs. Black grape juice was spray-dried at an inlet temperature of 160°C using different concentrations of MD (25, 30, 35, 40, 45, and 50%, w/v). The MD concentrations of 40% and 50% yielded the highest powder recovery (50.06–50.38%). The concentration of EA (40%, w/v) and inlet temperature (160°C) were selected to compare the efficacy of MD and the combination of MD and GA (MD+GA) at a ratio of 8:1. A higher total monomeric anthocyanin content (TMAC) (8.69 mg/100 g dry matter [DM]) and lower moisture content (~1.681%) were observed in MD+GA. Spray-drying at an inlet temperature of 180°C significantly (p < 0.05) enhanced TMAC and antioxidant activity and produced the smoothest particle surfaces, compared to 150°C, 160°C, and 170°C. These findings offer valuable insights for the food industry into optimizing encapsulation strategies and processing conditions to enhance stability and physicochemical properties of anthocyanins in black grape juice powder.